Cumulative lifetime violence, gender, social determinants of health and mental health in Canadian men: a latent class analysis - Scott-Storey, Kelly (Journal of family violence, 2024)
Purpose: Among men, violence is pervasive and associated with poor mental health, but little is known about which men are most vulnerable. Our purpose is to address this gap by exploring mental health and social determinants of health (SDOH) including gender role conflict (GRC) in heterogenous groups of men with distinct patterns of cumulative lifetime violence (CLV) as target and perpetrator. Methods: Latent class analysis was conducted using means of 64 indicators of CLV severity collected from a community sample of 685 eastern Canadian men, ages 19 to 65 years. Class differences by SDOH, and depression, anxiety, and posttraumatic stress disorder (PTSD) were explored with Chi-square and analysis of variance. Results: A 4-class solution was optimal. Class 1 had the lowest CLV severity; were more likely to be better educated, employed, and have little difficulty living on their incomes; and had better mental health than other classes. Class 2, characterized by moderate psychological violence as both target and perpetrator, had mean depression and PTSD scores at clinical levels, and more difficulty living on income than Class 1. Classes 3 and 4 were typified by high severity CLV as target but differentiated by Class 4 having the highest perpetration severity, higher GRC, and being older. In both classes, mean mental health scores were above cut-offs for clinical symptomology and higher than Classes 1 and 2. Conclusion: This is the first evidence that distinct patterns of CLV severity among men intersect with GRC and SDOH and are uniquely associated with mental health.